Gerenciamento de resultado: o impacto do ciclo de vida organizacional e da adoção de IFRS - Costa Filho, Francisco Carlos da (2018)
The earnings management can be understood as a distorted and intentional representation of the firm's economic performance, resulting from the manipulation of results that, in turn, may have different aims. These practices are influenced by several factors, including the firm’s life cycle, since its identification defines business characteristics and that make decisions more aligned with organizational reality. Another factor that can change the earnings management is the adoption of International Financial Reporting Standards (IFRS), in order to improve the quality of information and allow comparisons between international organizations, in addition to factors that are associated at the corporate and jurisdictional level. For this reason, the present study investigates the influence of stages of firm life cycle and adoption of IFRS in the earnings management. This is a descriptive and quantitative study. More than 34,000 companies from 125 countries were analyzed from 2002 to 2016. For the measurement of the earnings management, a dependent variable, it is adopted the model of Jones (1991) modified by Dechow, Sloan and Sweeney (1995) for accruals; Roychowdhury's (2006) model for management through operational decisions, also known as real activities manipulation; and McVay (2006) for classifications shifting. For the independent variables, the firm life cycle stages are used, according to the model proposed by Dickinson (2011) based on the company's cash flows and variable for adoption of IFRS. Among the results obtained, there is a greater number of companies in the maturity stage, and that earning management practices differ among stages. To test the hypotheses, panel data are used, and it can be seen that IFRS adoption negatively influences accruals and real activities manipulation, while life-cycle stages exert distinct effects, in particular the maturity stage, that is able to negatively influence all approaches of earnings management. The combined effect of the life cycle and the adoption of IFRS was only perceived on real activities manipulation. It is important to emphasize that the classification shifting was not affected by any of the variables under study. Therefore, considering the sample of this research, it is concluded that the firm life cycle and the adoption of IFRS are able to influence the practice of earnings management. However, it does not allow the confirmation of the precepts of the theory of the agency, since the manager, besides having more information, better understands the stage in which the organization is, thus opting for different methods of earnings management.